Strategi Pondok Pesantren Daarul Huda Li-Tahfidhil Qur'an Malang dalam Membentuk Akhlaqul Karimah Santri di Era Modern - Saisatul Munawwaroh; Choeroni Choeroni; Khoirul Anwar (CV. Berkah Cakrawala Inspirasi, 2026)
This research examines the strategies employed by Pondok Pesantren Daarul Huda Li-Tahfidhil Qur'an Malang in shaping the noble character (akhlaqul karimah) of its students in the modern era. This study aims to identify comprehensive strategies implemented by the pesantren in maintaining traditional Islamic values while adapting to contemporary challenges. Using a qualitative descriptive approach, data were collected through observation, in-depth interviews with kyai, ustadz, and students, as well as document analysis. The findings reveal that the pesantren employs five integrated strategies: (1) curriculum integration combining Qur'anic memorization with character education through kitab kuning such as Ta'limul Muta'allim and Akhlaq Lil Banin, (2) exemplary leadership from kyai and ustadz who serve as role models in daily interactions, (3) structured habituation through strict daily routines including congregational prayers and tahfidz schedules, (4) conducive environmental support with 24-hour boarding system, and (5) active parental involvement through regular communication. The main challenges include social media influence and diverse student backgrounds, which are addressed through digital literacy education and intensive orientation programs. This study concludes that the success of character formation depends on synergy among all components and consistent implementation of established Islamic values.